Cromoglycate and Nedocromil: Influence on Airway Reactivity - E. A. Valletta; A. L. Boner (Hindawi Limited, 1994)
Although basic mechanisms of bronchial hyper-responsiveness (BHR) are still incompletely understood, inflammation of airways is likely to play a fundamental role in modulating BHR in patients with asthma. The involvement of several inflammatory cells (eosinophils, mast cells, lymphocytes, neutrophils, macrophages and platelets) and of bioactive mediators secreted by these cells in the pathogenesis of asthma is well documented. Sodium cromoglycate and nedocromil sodium are two pharmacological agents which have anti-allergic and anti-inflammatory properties. Their clinical effectiveness in mild to moderate asthma, and the capacity to reduce BHR under different natural and experimental conditions, make them valuable drugs for maintenance therapy in patients with asthma.